Evaluation of thermal behavior for an asymmetric greenhouse by means of dynamic simulations (2014)
In this paper is presented the design of an asymmetric greenhouse, with a simulation and evaluation of its microclimate by means of DesignBuilder®. Climatic and geographical conditions of the greenhouse location are processed with DesignBuilder®, which also allows to include the geometrical characteristics of the enclosure and its roofing, the properties of its building materials and a description of the climate control system. Three configurations of this asymmetric greenhouse are evaluated in order to analyze and compare their internal gains.